1994
DOI: 10.1164/ajrccm.150.4.7921452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high frequency chest compression and conventional chest physiotherapy in hospitalized patients with cystic fibrosis.

Abstract: Clearance of bronchial secretions is essential in the management of cystic fibrosis (CF) patients admitted for acute pulmonary exacerbation. Conventional physiotherapy (CPT) is labor-intensive, time-consuming, expensive, and may not be available as frequently as desired during hospitalization. High frequency chest compression (HFCC), which uses an inflatable vest linked to an air-pulse delivery system, may offer an attractive alternative. To study this, we prospectively studied 50 CF patients admitted for acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
1
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 18 publications
1
67
1
5
Order By: Relevance
“…Physical techniques such as breath stacking and assisted cough, as well as medication management (bronchodilators, anticholinergic agents), have become increasingly common in aggressive multidisciplinary treatment settings. In addition, use of intrasalivary gland injection of botulinum toxin has been shown to result in significant improvement of sialorrhea and improve respiratory insufficiency [130,131].…”
Section: Respiratory Therapiesmentioning
confidence: 99%
“…Physical techniques such as breath stacking and assisted cough, as well as medication management (bronchodilators, anticholinergic agents), have become increasingly common in aggressive multidisciplinary treatment settings. In addition, use of intrasalivary gland injection of botulinum toxin has been shown to result in significant improvement of sialorrhea and improve respiratory insufficiency [130,131].…”
Section: Respiratory Therapiesmentioning
confidence: 99%
“…At T1 we also measured the patient's subjective discomfort with a 0 -100% discomfort visual analog scale. 20 We also measured the volume and wet and dry weight of collected sputum. We asked the patients about adverse effects throughout the 30-min treatment session and at T3.…”
Section: Measurementsmentioning
confidence: 99%
“…Additionally, CPT is labor-intensive, and low treatment adherence rates, hypoxemia, and discomfort have been reported among patients. 3 Evidence indicates that CPT can provide effective airway clearance, preserving pulmonary function and minimizing complications. Researchers in many studies 4,5 have reported small-scale benefit of CPT on pulmonary end points.…”
mentioning
confidence: 99%
“…7 As an alternative, contemporary high-frequency chest wall oscillation (HFCWO) may increase rates of lung recovery thanks to the technique's controlled electronic selections of frequency and pressure amplitude. 8,9 Previous comparative studies 3,10,11 have shown HFCWO to be as effective as CPT in clearing pulmonary secretions among patients with chronic pulmonary disease in mostly outpatient settings. Additionally, HFCWO is not operator-dependent, does not require specialized positions, and may be less painful than CPT.…”
mentioning
confidence: 99%
See 1 more Smart Citation